2016
DOI: 10.1002/nau.23161
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term course of sacral anterior root stimulation in spinal cord injured individuals: The fate of the detrusor

Abstract: The detrusor pressure during sacral anterior root stimulation decreases over time in SCI individuals. However, the changes do not seem to be clinically relevant during the first decade after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For instance, pressure flow studies in subjects without any known urological pathology have also indicated a lower detrusor contractility in women compared to men and a higher peak detrusor pressure and higher detrusor pressure during maximum flow rate in men compared to women 25,31,32 . A higher maximum detrusor pressure was also maintained in men compared to women with a spinal cord injury and undergoing sacral anterior root stimulation to facilitate voiding 33 . Animal studies also provide support to the notion of sexual dimorphism of detrusor function, as a higher maximum flow rate and longer micturition time were shown in male compared to female rats undergoing cystometry 34 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, pressure flow studies in subjects without any known urological pathology have also indicated a lower detrusor contractility in women compared to men and a higher peak detrusor pressure and higher detrusor pressure during maximum flow rate in men compared to women 25,31,32 . A higher maximum detrusor pressure was also maintained in men compared to women with a spinal cord injury and undergoing sacral anterior root stimulation to facilitate voiding 33 . Animal studies also provide support to the notion of sexual dimorphism of detrusor function, as a higher maximum flow rate and longer micturition time were shown in male compared to female rats undergoing cystometry 34 .…”
Section: Discussionmentioning
confidence: 91%
“…Differences between males and females with regards to detrusor contractility and bladder pressures during micturition have been attributed to a greater outflow resistance in males 27,33,36 . The striated EUS muscle is well developed in male but not female rats 35 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the selection process, 38 articles were retained for analysis including 24 retrospective studies (5-28), 4 prospective studies (29-32), 4 cross-sectional studies (33-36), 4 case reports (37-40), 1 survey (41) and 1 basic research article (42). Among these publications, 6 dealt with individuals quality of life (29,30,33-36), and 8 others including two case reportswere placed in the category "Other considerations" (5,6,(37)(38)(39)(40)(41)(42). The axes "Benefits for visceral functions" and "Implantation procedure and reliability" regrouped the 24 remaining publications.…”
Section: Research Process and Study Designmentioning
confidence: 99%
“…Eight publications were retained to complement this review as they were dealing with aspects little or not documented in previous studies (Table 5; 204 individuals from level IV or V studies including 4 case studies). Among these papers, six dealt directly with the consequences of implantation (5,6,(37)(38)(39)(40), while the last two (41,42) were focused on the prospects of this design of implant. (41) attempted to identify patients' preferences for future neuroprostheses and highlighted the major role of the benefit-risk ratio on implant acceptability.…”
Section: Additional Informationmentioning
confidence: 99%
“…For example, sacral nerve stimulation (SNS) [4] therapy and transcutaneous tibial nerve stimulation (TTNS) [57] therapy have been used to treat subjects with SCI and NDO. Although both TTNS and SNS therapies have been reported to significantly improve urinary continence by increasing bladder capacity in subjects with incomplete SCI [57], a few recent studies report that TTNS and SNS did not produce a satisfactory outcome in related clinic trials [8, 9]. Moreover, these two neuromodulation approaches are not effective for increasing bladder capacity in individuals with complete SCI; it is still unclear why both approaches failed to improve urinary continence in these individuals.…”
Section: Introductionmentioning
confidence: 99%